4x-6(9-x)=13

Simple and best practice solution for 4x-6(9-x)=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-6(9-x)=13 equation:


Simplifying
4x + -6(9 + -1x) = 13
4x + (9 * -6 + -1x * -6) = 13
4x + (-54 + 6x) = 13

Reorder the terms:
-54 + 4x + 6x = 13

Combine like terms: 4x + 6x = 10x
-54 + 10x = 13

Solving
-54 + 10x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '54' to each side of the equation.
-54 + 54 + 10x = 13 + 54

Combine like terms: -54 + 54 = 0
0 + 10x = 13 + 54
10x = 13 + 54

Combine like terms: 13 + 54 = 67
10x = 67

Divide each side by '10'.
x = 6.7

Simplifying
x = 6.7

See similar equations:

| 5x-3=3x+33 | | 4r^2=r | | 12y-108=0 | | (5-5)(5x+2)=0 | | 6x-3y=-8 | | 18-2x=-8x+12 | | 7.2x-4.1=11.2 | | -4x=-42+3x | | 7.6x-8.3=14.5 | | 9.2x+5.514=158.234 | | y=2x^2-7x+12 | | 2.1x+2.48=5 | | 7x-17=-73 | | 9-12+5p=14+2 | | 25x^2=10 | | 7m^8-7=0 | | 5(-2b-7)+4b= | | 2z-26=-32+4z | | 2z-26=-32+42 | | 7p-22=-6+9p | | 6+3(x+5)= | | x^3-7x^2+x-18=0 | | 6(3+4x)-5=37 | | 3(2+4)= | | -6x-8= | | 2x-45=90(2x)-3 | | -12x=48 | | 6x^2-8x-3=5 | | 4x^2-3=11x | | 1.74x+x=1 | | 2x+4=4x-5 | | x/2-1=/5-7 |

Equations solver categories